Infarct-related artery occlusion, tissue markers of ischaemia, and increased apoptosis in the peri-infarct viable myocardium - Abbate, Antonio; Bussani, Rossana; Biondi-Zoccai, Giuseppe G.L.; Santini, Daniele; Petrolini, Alessandro; Giorgio, Fabio De; Vasaturo, Fortunata; Scarpa, Susanna; Severino, Anna; Liuzzo, Giovanna; Leone, Antonio Maria; Baldi, Feliciano; et al. (European heart journal, 2005)
Aims Unfavourable cardiac remodelling often complicates acute myocardial infarction (AMI) as a result of increased cardiomyocyte apoptosis. It is currently unclear whether ongoing or recurrent ischaemia is an independent determinant for increased apoptosis in peri-infarct viable myocardium. Methods and results In order to assess the link between infarct-related artery (IRA) occlusion, ischaemia, and apoptosis, 30 subjects dying 7–120 days after AMI (16 with IRA occlusion and 14 with patent IRA) and five control subjects were selected at autopsy. Cardiomyocytes were defined as apoptotic if co-expressing TUNEL and activated caspase-3. Expression of both hypoxia-inducible factor-1 and cyclo-oxygenase-2 was assessed in the peri-infarct myocardium and considered as tissue markers of ischaemia. Evidence of ischaemia was significantly more frequent in cases with IRA occlusion (53%) than in cases with patent IRA (15%) or control hearts (0%, P=0.026). The finding of IRA occlusion and markers of ischaemia identified cases with higher apoptotic rates (ARs) in the peri-infarct viable myocardium [12.2% (8.2–14.0), P<0.001 vs. others], whereas IRA occlusion without ischaemia was associated with lower AR, not significantly different from patent IRA [3.0% (1.0–7.9) vs. 2.2% (1.0–5.8), respectively, P=0.42] Conclusion Ischaemia in the peri-infarct viable myocardium is present in over 50% of subjects dying late after AMI with IRA occlusion, and it is associated with increased apoptosis. Relief of ischaemia after AMI may prove of benefit in preventing apoptosis and its consequences.